Tackling the Global Profitarchy : Gender and the Choice of Business Sector - Goldstein, Markus; Gonzalez Martinez, Paula; Papineni, Sreelakshmi (World Bank, Washington, DC, 2019)
Sectoral segregation is often used to explain a large part of a well-documented gender earnings gap in business profits. Women tend to sort into different sectors than men, and the sectors dominated by women tend to be less profitable. This paper investigates the horizonal dimension of sectoral segregation by studying global data on female and male enterprises operating in sectors that are typically dominated by the same and opposite sex. The analysis uses the novel Future of Business dataset, which spans 97 countries and was administered to enterprise owners, managers, and employees who use Facebook. The analysis finds that some of the earnings gap can indeed be explained by sector choice: female-owned businesses in male-dominated sectors make significantly higher profits than those in traditionally female sectors. The evidence points to a hierarchy of earnings, with male-owned businesses in male-dominated sectors earning the most, women in male-dominated sectors and men in female-concentrated sectors in the middle tier, and women in female-concentrated sectors at the bottom. Correlational analysis suggests that women who own businesses in male-dominated sectors are younger, married, and more likely to have inherited the business than women in female-concentrated sectors. They have similar education to women in female-concentrated sectors and present higher self-efficacy but lower entrepreneurial identity and commitment to the sector. Male support networks appear to be key for female-owned firms, with co-ownership with husbands and male role models factoring into the decision to cross over.